2018
DOI: 10.5664/jcsm.7258
|View full text |Cite
|
Sign up to set email alerts
|

The Epworth Sleepiness Scale: Validation of One-Dimensional Factor Structure in a Large Clinical Sample

Abstract: Our study confirmed the unidimensionality of the ESS in a large diverse clinical population. Results from this study can be used to justify the interpretation of the ESS within clinical populations, and supports valid comparisons between groups based on the ESS. Future studies are warranted to further understand the items comprising the ESS and potentially eliminate redundant items for increased efficiency in clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 35 publications
1
36
0
1
Order By: Relevance
“…Inclusion criteria for recruitment were severe COPD, defined as Global Initiative for Chronic Obstructive Lung Disease (GOLD) stage 3–4 criteria with FEV1/FVC < 0.70, FEV1 < 50%, and hypoxemic respiratory failure, defined as the need for supplemental oxygen at rest or with exertion. Patients with obstructive sleep apnea or obesity hypoventilation syndrome were excluded from the study, and all patients were low risk (<10) based on the Epworth sleepiness scale [ 34 ]. Patients with history of a neuromuscular disorder were also excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion criteria for recruitment were severe COPD, defined as Global Initiative for Chronic Obstructive Lung Disease (GOLD) stage 3–4 criteria with FEV1/FVC < 0.70, FEV1 < 50%, and hypoxemic respiratory failure, defined as the need for supplemental oxygen at rest or with exertion. Patients with obstructive sleep apnea or obesity hypoventilation syndrome were excluded from the study, and all patients were low risk (<10) based on the Epworth sleepiness scale [ 34 ]. Patients with history of a neuromuscular disorder were also excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Items range from 0 (no chance of dozing) to 3 (high likelihood of dozing), and total scores range from 0–24, with higher values representing increased daytime sleepiness. The ESS is a standard clinical and research tool that is well validated [ 33 ]. The ESS was previously translated into Spanish [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…a pictorial version for patients with diminished literacy skills), making it accessible worldwide. In addition, the ESS has high internal consistency in measuring EDS in patients with OSA [11,40]. In general, studies have found the ESS to have good test-retest reliability in controlled clinical trial settings or when administered in similar clinical settings, and less reliability when administered across different primary and secondary care settings (e.g.…”
Section: Self-report Assessments Of Edsmentioning
confidence: 99%